Modeling the Intelligent Transport Systems Elements Functionality Testing Plan: A Case Study - Lizbetin, Jan; Pecman, Jan; Hanzl, Jiri; Stopka, Ondrej (Communications - Scientific Letters of the University of Zilina, 2022)
Autonomous control and the associated development of relevant intelligent control systems have become an issue of interest in the automotive sector decades ago. This article deals with the issue of subsystem validation planning. The theoretical part describes the issue, characterizes the current state of the researched issues in selected scientific publications and characterizes the data and methods with which the authors work. The practical part of the article analyzes a case study in the form of a model project, its structure, testing requirements and design of a test campaign plan. The output is a calculation and decision tree, which determines the optimal variant of the number of vehicles so that the validation is completed, while minimizing time and financial resources.
Keywords: autonomous management; testing; planning; intelligent transport systems